Specific features of thermal expansion and polyamorphism in CH4-C60 solutions at low temperatures - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Gadd, ,G.E.; Moricca, S.; Cassidy, D.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The temperature dependence of the linear thermal expansion coefficient a(T) has been investigated in the temperature range of 2.5 to 23 K for two different CH4-C60 solutions in which CH4 molecules occupied 24 and 50% of the octahedral interstitial sites of the C60 lattice. In both cases, a(T) exhibits hysteresis, suggesting the existence of two types of orientational glass associated with these solutions. The temperature of the first-order phase transition between these two glasses was estimated and the behavior of these two glasses compared. The characteristic times of thermalization t1, reorientation of the C60 molecules t2, andof the phase transformation between the glasses t', have been estimated for these solutions. Both the temperature dependence of a(T) and the characteristic thermalization time t1 are found to have features near the phase transition temperature and an explanation has been put forward to explain these observed features.